Industrial Engineering 4.0 Strategies to Improve Manufacturing Efficiency and Productivity - Maharjan, Kailie; Elliot, McCarty; Oscar, Scherschligt (Journal of Moeslim Research Technik, 2024)
The Industrial Revolution 4.0 has brought significant changes in the manufacturing sector through the application of advanced technologies such as the Internet of Things (IoT), artificial intelligence (AI), and big data analytics. The application of these technologies aims to address the challenges of improving efficiency and productivity in an increasingly complex and competitive manufacturing environment. This research aims to identify and analyse effective strategies in implementing Industry 4.0 techniques to improve operational efficiency and productivity in the manufacturing sector. This research uses a case study method on several manufacturing companies that have implemented Industry 4.0 technology. Data were collected through interviews, direct observation, and analysis of company documents. Qualitative and quantitative approaches were used to analyse the data obtained. The results showed that the implementation of IoT, AI, and big data analytics technologies significantly improved efficiency and productivity. Successful implementation involves good integration between technology and business processes, employee training, and commitment from top management. Companies that implement these strategies successfully reduce downtime, improve product quality, and speed up production time. The research concludes that the right Industry 4.0 strategy can deliver significant improvements in manufacturing efficiency and productivity. The key to success lies in thorough technology integration, improved workforce competencies, and strong management support. Effective implementation of these strategies can give companies a competitive advantage in the global market